2010
DOI: 10.1021/ja101793a
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Synthesis of Cyclobutylboronates through Copper(I)-Catalyzed Reaction of Homoallylic Sulfonates and a Diboron Derivative

Abstract: A copper(I)-catalyzed stereospecific reaction for the preparation of cis- and trans-1-silyl-2-borylcyclobutanes as well as 1-phenyl-2-borylcyclobutanes is reported. (Z)- and (E)-Homoallylic methanesulfonates were converted to the corresponding trans- and cis-cyclobutane derivatives, respectively, in the presence of a CuCl/dppp catalyst, bis(pinacolato)diboron, and K(O-t-Bu)/THF. Stereospecific derivatizations of the cis- and trans-borylcyclobutanes were carried out to demonstrate the utility of the borylcyclob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
53
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(54 citation statements)
references
References 25 publications
0
53
0
1
Order By: Relevance
“…This model performs well over pericyclic reactions, and has been successfully applied to the 1,3-dipolar cycloaddition, [2,3] the Diels-Alder, [4] and the Ene reaction. [5] On the other hand, among the methods to synthesize cyclobutane motifs, [6][7][8][9][10] the also pericyclic [2 + 2] cycloaddition reaction remains as one of the most powerful strategies, leading to a 4-membered ring in a single step with high selectivity and perfect atom economy. Forbidden by orbital symmetry in the electronic ground-state, a widely used approach requires excitations induced by light to link the alkene units, sometimes with the assistance of a photosensitizer like Cu(I) triflate.…”
Section: Introductionmentioning
confidence: 99%
“…This model performs well over pericyclic reactions, and has been successfully applied to the 1,3-dipolar cycloaddition, [2,3] the Diels-Alder, [4] and the Ene reaction. [5] On the other hand, among the methods to synthesize cyclobutane motifs, [6][7][8][9][10] the also pericyclic [2 + 2] cycloaddition reaction remains as one of the most powerful strategies, leading to a 4-membered ring in a single step with high selectivity and perfect atom economy. Forbidden by orbital symmetry in the electronic ground-state, a widely used approach requires excitations induced by light to link the alkene units, sometimes with the assistance of a photosensitizer like Cu(I) triflate.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, pioneering investigations by Ito, Suginome and their co‐workers have led to the development of inter‐6 as well as intramolecular7 Pt‐catalyzed boron–silicon additions to alkyl‐substituted alkenes. Another noteworthy advance by Ito, Toyoda, and Sawamura illustrates that Cu–phosphine catalysts can promote copper–boron addition to aliphatic vinylsilanes 8. More recently, it has been shown that activation of a B–Si bond with KO t Bu in the presence of aryl alkenes results in the formation of the corresponding borosilanes 9.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Inspired by certain ring-opening strategies applied to similar heterobicyclic photoproducts, [9] we envisioned that cleavage of the BÀN bond in 1 (Scheme 2) could lead to an unfused cyclobutane bearing vicinal boron and nitrogen substituents with predetermined cis relative stereochemistry. [10,11] Thep resence of boron in place of the usual carbonyl group found in the systems alluded to above was subsequently viewed as an opportunity to readily functionalize the corresponding position on the cyclobutane ring by fundamentally different means.…”
mentioning
confidence: 99%